The Influence of Digital Economic Literacy on Digital Marketing Competence for Women's Communities in Rural Areas - Purnomo, Purnomo; Sutarni, Nani; Nuraeni, Lenny; Komara, Diemas Arya; Inoue, Hiromu (Journal of Nonformal Education, 2026)
Background  The digital divide persists in rural Indonesia, where many women entrepreneurs remain largely excluded from digital economic activities. This gap is particularly urgent because it restricts women-led MSMEs from competing effectively in an increasingly digital marketplace.Research Urgency  Addressing this gap is urgently needed as low digital economic literacy among housewives in rural areas continues to hinder effective digital marketing practices. Therefore, targeted interventions are necessary to strengthen digital capabilities within rural women's communities.Research Objectives  This study analyzes the influence of digital economic literacy on digital marketing competency among women in the Local Hero Community in Lampegan Village, Ibun District, Bandung Regency, Indonesia.Research Method  A quantitative approach with a survey method was employed. Questionnaires using a Likert scale (1–5) were distributed to all 25 members (census study) of the Local Hero Women's Community. Data were processed using simple linear regression analysis.Research Findings  Digital economic literacy positively and significantly influences digital marketing competency (R² = 0.715; p < 0.001; t-calculated = 7.953 > t-table = 1.714). Digital economic literacy explains 71.5% of variance in digital marketing competency, with the regression equation Y = 10.354 + 0.867X.Research Conclusion  Strengthening digital economic literacy significantly improves rural women's digital marketing competencies. The WanojaMart local marketplace serves not merely as a transactional platform but as a digital economic school, supporting sustainable women's empowerment aligned with SDG 5 (Gender Equality) and SDG 8 (Decent Work and Economic Growth).Research Novelty  This study uniquely connects digital economic literacy with a locally embedded digital ecosystem (WanojaMart marketplace), demonstrating that effective women's empowerment requires a context-specific supportive network, not merely access to technology.